Studi Literature: Analisis Konsep Pengembangan Modul Ajar Hypercontent Berbasis Multiplatform - Hotimah Hotimah (Journal on Education, 2023)
Given their role and function in the learning process, the availability of teaching materials or teaching modules is crucial. Considering the characteristics of students as digital natives, who differ from those of previous generations, it is essential to present instructional modules that align with current technological advancements. The creation of multiplatform-based hyper-content education modules is both a challenge and a means of facilitating the learning process for students. By presenting tools in the form of hypertext, various website platforms, YouTube, QR code, and Cloud Computing, this hyper content teaching module will allow students to learn according to their learning styles and characteristics, increase interest in learning, and prevent destructive technology from occurring for educational implementers. Especially if the development of this hyper-content module follows the TPACK methodology.